HR Recruitment Through Chatbot- An Innovative Approach - DR. GIGI G.S; GUNASEELI. S, MS. PRISCILLA (The journal of contemporary issues in business and government, 2020)
Artificial Intelligence is used in all the sectors, among which chatbot is a new trend. Chatbots are used in many sectors, where HR chatbot have taken over the HR industry This research paper titled HR Recruitment through chatbot helps to know about how chatbot is useful in recruitment for HR managers and to know whether these chatbots will replace hiring managers in the upcoming years or not. A descriptive research is used in the study for a sample size of 113. The tools used in the study are mean analysis, frequency analysis, Independent sample T test and ANOVA. It is found that factors influencing the study are need for chatbot, technical issue, evaluation and installation. From the study it’s been inferred that chatbot can help the HR manager in saving their time by selecting the qualified and helping the HR manager by bringing the recruitment to further process but it can’t replace a HR manager.